Perceraian Akibat Ketidakharmonisan Dalam Rumah Tangga Antara Ry dan Tr - Purba, Eugenia Priscilla; Annurillah, Riksya; Mourinho, Nigeel Jose; Zinan, Zalfa (Media Hukum Indonesia (MHI), 2025)
The divorce of celebrity Ria Yunita (Ria Ricis) with Teuku Rushariandi has become a public spotlight and reflects the social and emotional dynamics in the lives of celebrity families. This study analyzes the factors that influence the decision to divorce, such as poor communication, differences in values, and external pressure from the entertainment world. Through a qualitative approach in the form of social media analysis, interviews, and related sources, this study focuses on the impact of divorce on Ria Ricis' personal and professional life, as well as the social stigmatization that often accompanies celebrities after divorce. This studi is expected to provide more insight into the influence of social pressure on marital relationships and the challenges faced by celebrities in overcoming household problems.